Selenium-Induced Toxicity Is Counteracted by Sulfur in Broccoli (Brassica oleracea L. var. italica) - Tian, Ming; Hui, Maixia; Thannhauser, Theodore W.; Pan, Siyi; Li, Li (Frontiers in Plant Science, 2017)
Selenium (Se) is an essential micronutrient for humans. Increasing Se content in food crops offers an effective approach to enhance the consumption of Se in human diets. A thoroughly understanding of the effects of Se on plant growth is important for Se biofortification in food crops. Given that Se is an analog of sulfur (S) and can be toxic to plants, its effect on plant growth is expected to be greatly affected by S nutrition. However, this remains to be further understood. Here, we evaluated the influence of Se treatments on broccoli (Brassica oleracea L. var. italica) growth when S was withheld from the growth nutrient solution. We found that Se was highly toxic to plants when S nutrition was poor. In contrast to Se treatments with adequate S nutrition that slightly reduced broccoli growth, the same concentration of Se treatments without S supplementation dramatically reduced plant sizes. Higher Se toxicity was observed with selenate than selenite under low S nutrition. We examined the bases underlying the toxicity. We discovered that the high Se toxicity in low S nutrition was specifically associated with an increased ratio of Se in proteins verse total Se level, enhanced generation of reactive oxygen species, elevated lipid peroxidation causing increased cell membrane damage, and reduced antioxidant enzyme activities. Se toxicity could be counteracted with increased supplementation of S, which is likely through decreasing non-specific integration of Se into proteins and altering the redox system. The present study provides information for better understanding of Se toxicity and shows that adequate S nutrition is important to prevent Se toxicity during biofortification of crops by Se fertilization.